Integrating Digital Green Accounting into Business Education: A Review and Future Directions for Sustainable E-Business Learning - Md Sajid Hasan; Sheikh Abu Toha Md Saky; Dr. Md Nurul Islam (Universitas Negeri Semarang, 2026)
The integration of digital green accounting into e-business and business education represents a critical step toward aligning technological innovation with sustainability imperatives. This study conducts a narrative literature review of research published between 2005 and 2025, examining how digital tools such as blockchain, artificial intelligence, IoT, and big data are reshaping accounting practices to enhance transparency, accountability, and environmental stewardship. Findings reveal that while e-businesses increasingly adopt green accounting to align with Environmental, Social, and Governance (ESG) frameworks and the Sustainable Development Goals (SDGs), challenges such as curriculum rigidity, limited faculty expertise, and technological constraints hinder widespread adoption in business education. Nonetheless, innovative pedagogical practices including experiential learning, simulations, and industry partnerships which offers promising pathways for embedding sustainability literacy and digital skills into curricula. A conceptual framework is proposed to guide the integration of digital green accounting into academic programs, highlighting inputs, processes, outputs, and long-term impacts. The study concludes that collaboration among academia, industry, and policymakers is essential for preparing future business leaders to balance profitability with sustainability and drive systemic transformation.